A two-phase liquid immersion cooling strategy utilizing vapor chamber heat spreader for data center servers. (25th June 2022) - Zhou, Guohui; Zhou, Jingzhi; Huai, Xiulan; Zhou, Feng; Jiang, Yawen
Highlights: A two-phase liquid immersion cooling strategy for servers was developed. Gradient capillary wicking structures were employed in the vapor chamber. Thermal performance of the vapor chamber was carefully evaluated. A minimum total thermal resistance of 0.05 °C/W was obtained at 500 W. Abstract: The 5th generation communication technology dramatically increases the cooling demands of data center servers, and the thermal management strategies should possess the crucial characteristics of relatively compact structure, high cooling efficiency, and reliable operation as well as energy saving. In general, cooling electronics effectively could significantly drive the efficient power utilization for the electronic devices. As an efficient heat dissipation solution, liquid immersion cooling is a potential and prominent candidate to cool high-power-density electronics by submerging them into a pool of dielectric liquid. In this paper, a two-phase liquid immersion cooling strategy using vapor chamber heat spreader was developed and investigated to tackle the continuously increasing demands in heat dissipation of data center servers. In order to promote the circulation of the working liquid and improve the heat transfer performance, gradient capillary wicking structures were innovatively employed in the vapor chamber. Systematic experimental investigations were conducted to fully study the thermal performance of the vapor chamber. The results indicated that the vapor chamber could effectively transport 500 W heat load with the heat source temperature below 85 °C, and could cope with a maximum heat load up to 900 W without dry-out, at which a vapor chamber thermal resistance of 0.046 °C/W was attained. Additionally, compared to other advanced cooling methods reported in literatures, the proposed two-phase liquid immersion cooling strategy using the vapor chamber exhibited a higher heat transfer performance, providing a promising means for high-power data center servers cooling.